2000
DOI: 10.1074/jbc.m003936200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Structural Elements Important for Matrix Metalloproteinase Type V Collagenolytic Activity as Revealed by Chimeric Enzymes

Abstract: Digestion of type V collagen by the gelatinases is an important step in tumor cell metastasis because this collagen maintains the integrity of the extracellular matrix that must be breached during this pathological process. However, the structural elements that provide the gelatinases with this unique proteolytic activity among matrix metalloproteinases had not been thoroughly defined. To identify these elements, we examined the substrate specificity of chimeric enzymes containing domains of gelatinase B and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 54 publications
4
55
0
Order By: Relevance
“…Gelatinases MMP2 and MMP9 digest type IV and V collagens in basement membranes to facilitate tissue growth and remodeling (Zeng et al 1999, O'Farrell & Pourmotabbed 2000. Both MMP2 and MMP9 were detected in the murine uterus (Hu et al 2004) and human endometrial cells (Martelli et al 1993, Iwahashi et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Gelatinases MMP2 and MMP9 digest type IV and V collagens in basement membranes to facilitate tissue growth and remodeling (Zeng et al 1999, O'Farrell & Pourmotabbed 2000. Both MMP2 and MMP9 were detected in the murine uterus (Hu et al 2004) and human endometrial cells (Martelli et al 1993, Iwahashi et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…SHG imaging reveals Mmp9-dependent collagen remodeling in the hai1 morphants It is known that Mmp9 alters the ECM through the cleavage of matrix components, including collagen (Collier et al, 1988;O'Farrell and Pourmotabbed, 2000;Van den Steen et al, 2002). To determine whether Mmp9 modulates the collagen matrix in hai1 morphants we performed SHG imaging (Campagnola et al, 2002;Mohler et al, 2003).…”
Section: Mmp9 Depletion Partially Rescues the Hai1 Mutant Phenotypementioning
confidence: 99%
“…The Kcat/Km values for the fluorogenic peptide substrate were then obtained by assaying the enzymes at 23ºC using 1.5 M peptide substrate as previously described [99]. Assays were conducted under the condition where K m >> [S], and K cat /K m values were calculated from the following equation:…”
Section: Determination Of Kcat/km Values For the Fluorogenic Peptide mentioning
confidence: 99%
“…MMP-9 has an additional domain known as the gelatin binding domain composed of 3 homology fibronectin-type II modules of 58 amino acids inserted into the catalytic domain ( Figure 5-1b) [98]. We have shown that this domain is responsible for the type V collagen activity of the enzyme [40,99]. The carboxyl-terminal domain of MMP-9 is involved in anchoring the enzyme to CD44 [100][101][102] and binds to heparin [103].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation